Características químicas e morfogênicas de Megathyrsus maximus cv Aruana submetida à adubação nitrogenada em sistema silvipastoril e pleno sol - Baungratz, Andressa Radtke (2022)
The search for sustainable production systems is increasingly present in the production of pasture animals. Silvipastoral systems are an option whose characteristics increase productivity and the system as a whole. However, pastures that reach high productivity in certain times of the year, with high nutritional quality are a challenge. In this way, the use of chemical fertilization with nitrogen (N) is a viable strategy. The objective was to evaluate the morphogenetic, structural and productive characteristics and mineral composition of M. maximus under the influence of nitrogen fertilization in full sun and silvipastoral systems. The study was conducted for 84 days, divided into four experimental periods. The treatments evaluated were: (1) Aruana pasture in full sun with nitrogen fertilization, (2) Aruana pasture in full sun without nitrogen fertilization, (3) Aruana pasture in silvipastoral system with nitrogen fertilization and (4) Aruana pasture in silvipastoral system without nitrogen fertilization. Nutrient characterization, urinary excretion of N and the returned amount of the nutrient were determined from four lambs in a Latin square. Plant morphogenesis was influenced by the treatments and N fertilization promoted higher densities of tillers, aerial and basilar. Greater leaf area index was observed in the full sun system as well as the production of DM that was higher in the full sun system with fertilization. The chemical composition of leaves and stalks was positively influenced by the use of N fertilizer, while the contents of DM, ADF and NDF were higher without fertilizer. The treatments have not influenced the O.M. and O.C. contents of the soil. N contents in leaves and stalks were not influenced by the treatments, high P and K contents were observed in the silvipastoral system. Full sun combined with N fertilization provided better conditions for the development and bromatological chemical composition of forage.